Concomitant polymorphs of 1, 3‐bis(3‐fluorophenyl)urea. Issue 9 (26th August 2016) - Capacci-Daniel, Christina A.; Bertke, Jeffery A.; Dehghan, Shoaleh; Hiremath-Darji, Rupa; Swift, Jennifer A.
Abstract : 1, 3‐Bis(3‐fluorophenyl)urea crystallizes in two conformational polymorphs. The urea molecules assemble into one‐dimensional hydrogen‐bonded chains, which adopt antiparallel and parallel alignments in the two forms. Abstract : Hydrogen bonding between urea functionalities is a common structural motif employed in crystal‐engineering studies. Crystallization of 1, 3‐bis(3‐fluorophenyl)urea, C13 H10 F2 N2 O, from many solvents yielded concomitant mixtures of at least two polymorphs. In the monoclinic form, one‐dimensional chains of hydrogen‐bonded urea molecules align in an antiparallel orientation, as is typical of many diphenylureas. In the orthorhombic form, one‐dimensional chains of hydrogen‐bonded urea molecules have a parallel orientation rarely observed in symmetrically substituted diphenylureas.